Global, regional, and national causes of child mortality in 2008: a systematic analysis - Black, Robert E; Cousens, Simon; Johnson, Hope L; Lawn, Joy E; Rudan, Igor; Bassani, Diego G; Jha, Prabhat; Campbell, Harry; Walker, Christa Fischer; Cibulskis, Richard; Eisele, Thomas; Liu, Li; et al. (The Lancet (British edition), 2010)
Up-to-date information on the causes of child deaths is crucial to guide global efforts to improve child survival. We report new estimates for 2008 of the major causes of death in children younger than 5 years. We used multicause proportionate mortality models to estimate deaths in neonates aged 0–27 days and children aged 1–59 months, and selected single-cause disease models and analysis of vital registration data when available to estimate causes of child deaths. New data from China and India permitted national data to be used for these countries instead of predictions based on global statistical models, as was done previously. We estimated proportional causes of death for 193 countries, and by application of these proportions to the country-specific mortality rates in children younger than 5 years and birth rates, the numbers of deaths by cause were calculated for countries, regions, and the world. Of the estimated 8·795 million deaths in children younger than 5 years worldwide in 2008, infectious diseases caused 68% (5·970 million), with the largest percentages due to pneumonia (18%, 1·575 million, uncertainty range [UR] 1·046 million–1·874 million), diarrhoea (15%, 1·336 million, 0·822 million–2·004 million), and malaria (8%, 0·732 million, 0·601 million–0·851 million). 41% (3·575 million) of deaths occurred in neonates, and the most important single causes were preterm birth complications (12%, 1·033 million, UR 0·717 million–1·216 million), birth asphyxia (9%, 0·814 million, 0·563 million–0·997 million), sepsis (6%, 0·521 million, 0·356 million–0·735 million), and pneumonia (4%, 0·386 million, 0·264 million–0·545 million). 49% (4·294 million) of child deaths occurred in five countries: India, Nigeria, Democratic Republic of the Congo, Pakistan, and China. These country-specific estimates of the major causes of child deaths should help to focus national programmes and donor assistance. Achievement of Millennium Development Goal 4, to reduce child mortality by two-thirds, is only possible if the high numbers of deaths are addressed by maternal, newborn, and child health interventions. WHO, UNICEF, and Bill & Melinda Gates Foundation.